Leguminosean Members:A Promising Candidates for Phytodiversity and Economic Potentialities - Thomas, Binu; Farsana, K. (Indian Forester, 2018)
Through the present study a documentation of diverse Leguminosean members which are belonging to the families like Fabaceae, Caesalpiniaceae and Mimosaceae from different localities of Kavanur panchayath, Malappuram district, Kerala. The present results reveals that, there are about 56 species, which are belonging to 34 genera in these 3 families. The present analysis also highlights some economic potentialities of documented species such as curative efficacy, edible potentiality and other miscellaneous purposes. In addition to this, the nitrogen-fixing ability of many legumes provides an important source of biological nitrogen in agriculture and natural ecosystems.